Imperial and residential city of Vienna and its suburbs - Wagner, Jacob, 1704-1770 (engraver):::Creator::::::::::::; Fuhrmann, Matthias, 1697-1773 (author):::Contributor:::::::::::: (Vienna; Kraußischen Buchhandlung; Austria)
Map of Vienna, Austria.